Endorphin Massage Therapy for Dysmenorrhea in Adolescent Girls at Takwa High School Palembang - Novi Rida Eriyani (Lembaga Pengembangan Kinerja Dosen, 2024)
Dysmenorrhea is a gynecological complaint caused by an imbalance of the hormone progesterone in the blood, resulting in pain during menstruation which often occurs in women. One effort to treat menstrual pain is non-pharmacological therapy with endhorpine massage. The aim of the research was to analyze the effect of endorpine massage on dysmenorrhoea in young women at SMA Takwa Palembang. The research method uses quasi-experimental one group pretest and posttest. The population is all class X female students. The total sample was 28 people taken using purposive sampling technique. The research instrument used the Numeric Rating Scale (NRS) which was measured before after the endorphin massage. Results: The average pain scale before endorpine massage was 4.83 (moderate pain) with a maximum value of 6 and a minimum value of 4. In the second measurement, the average pain scale was 2.61 (mild pain) with a maximum value of 4 and a minimum of 2. Results paired t test obtained α 0.022 < 0.05. Conclusion: There is an effect of endorphin massage on dysmenorrhoea in young women at SMA Takwa Palembang. It is hoped that related parties will develop complementary therapies to treat menstrual pain in adolescents through education.